The theory of equilibrium growth - Dixit, Avinash K. (London : Oxford University Press, 1976)
This book aims to bridge the gap between elementary and advanced textbooks on growth theory, and to highlight and clarify the framework of inter-temporal equilibrium that underlies much of growth theory.
.
Includes bibliographical references: p. [194]-202 and index.
rpm 18/10/2017
Loans
Keywords: Equilibrium (Economics); Economic development